Phenol biosensors in environmental engineering - Erhan, Elif; Keskinler, Bülent; Korkut, Seyda (My University, 2008)
Phenol measurement performance of three different horseradish peroxidase-based enzyme electrodes was studied. Electrode A was operated in a flow-injection system, while Electrode B and C were used in batch experiments. Various phenolic compounds were tested at each electrode. The highest sensitivity was observed for the biosensor fabricated by Electrode A, which can measure lower phenol concentrations. Although the same enzyme was used, each working electrode gave response to different phenolics by different selectivity depending on electrode configuration. However, Electrode A, B, and C gave no response to phenol, catechol, and o-cresol, respectively. This is an abstract of a paper presented at the 18th International Congress of Chemical and Process Engineering (Prague, Czech Republic 8/24-28/2008). © 2012 Elsevier B.V., All rights reserved.
18th International Congress of Chemical and Process Engineering, CHISA 2008 -- Prague --
Keywords: Amperometric biosensor; Carbon nanotube; Immobilized horseradish peroxidase; Phenol derivatives; Polypyrrole, poly(glutaraldehyde)